Ucides cordatus cordatus (Linnaeus, 1763) (Crustacea, Decapoda): complete larval development under laboratory conditions and its systematic position - Rodrigues, Misael Domingues; Hebling, Nilton José [UNESP] (Sociedade Brasileira de Zoologia, 1989)
Six zoeal stages and the megalopa of the comestible crab Ucides cordatus cordatus (Linnaeus, 1763) are described and illustrated. The larvae were reared in the laboratory at temperature 25 ± 1ºC and water salinity of 24 ; duration of stages and survival rates were measured. Comparisons with the descriptions of the zoeal morphologic characters of Ocypodidae and Gecarcinidae permited to include definitively U. c. cordatus in the family Ocypodidae, subfamily Ocypodinae.